Pemanfaatan Lingkungan Sebagai Media Pembelajaran Pendidikan Jasmani Melalui Insersi Nilai-Nilai Tri Hita Karana - Gusti Ngurah Arya Yudaparmita; Wahjoedi; I Ketut Iwan Swadesi (Kamaya: Jurnal Ilmu Agama, 2021)
This research is based on the perception of students of the PGSD STAHN Mpu Kuturan Singaraja Study Program that the learning process of Physical Education from home is very tedious and not in accordance with educational goals. Limited learning facilities and equipment as well as lack of interaction with friends and lecturers become obstacles in the physical education learning process at home, forcing Physical Education lecturers to be more creative in empowering and optimizing the use of existing facilities and equipment, adjusting to the conditions of students and their homes. The research subjects were 40 students of the PGSD STAHN Mpu Kuturan Singaraja Study Program. Based on the research results, it can be concluded that: 1) the use of the environment as a learning media for Physical Education through the insertion of Tri Hita Karana values ​​can be viewed in terms of: the type of environmental media, the insertion of the Tri Hita Karana values ​​in learning and effectiveness; and 2) students' perceptions of the use of the environment as a physical education learning medium through the insertion of the Tri Hita Karana values, namely: (1) learning using environmental media is very easy to obtain at home; (2) learning with the insertion of Tri Hita Karana values ​​is more fun; (3) the use of the environment as a learning media for Physical Education through the insertion of the Tri Hita Karana values ​​which are effective in learning; (4) the use of the environment as a learning media for Physical Education through the insertion of Tri Hita Karana values ​​is very useful in the learning process; (5) the use of the environment as a learning media for Physical Education through the insertion of Tri Hita Karana values ​​makes students more active in participating in learning from home.